2007
DOI: 10.1002/jor.20396
|View full text |Cite
|
Sign up to set email alerts
|

Effect of variability in anatomical landmark location on knee kinematic description

Abstract: Small variability associated with identifying and locating anatomical landmarks on the knee has the potential to affect the joint coordinate systems and reported kinematic descriptions. The objectives of this study were to develop an approach to quantify the effect of landmark location variability on both tibiofemoral and patellofemoral kinematics and to identify the critical landmarks and associated degrees of freedom that most affected the kinematic measures. The commonly used three-cylindric open-chain kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 41 publications
1
35
0
1
Order By: Relevance
“…For example, the patellofemoral 195 flexion angle was dictated by the landmarks that were selected to define the long axis, and patellofemoral tilt was affected by flexion axis definition. These correspondences were also found by Morton et al in their probabilistic analysis examining the sensitivity of patellofemoral kinematics to anatomical landmark locations in a cadaver model [28].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…For example, the patellofemoral 195 flexion angle was dictated by the landmarks that were selected to define the long axis, and patellofemoral tilt was affected by flexion axis definition. These correspondences were also found by Morton et al in their probabilistic analysis examining the sensitivity of patellofemoral kinematics to anatomical landmark locations in a cadaver model [28].…”
Section: Discussionsupporting
confidence: 77%
“…However, the effect of the variation of the patellar coordinate system was not investigated. Several 30 investigators have quantified the repeatability [2, 12,[26][27][28] and sensitivity [11] of the creation of their particular patellar coordinate systems. Katchburian et al [29] conducted a thorough review of patellar kinematics and recommended the coordinate system described by Lafortune [30] as being the 'most useful', possibly because it follows the method suggested by Grood and Suntay [31].…”
Section: Introductionmentioning
confidence: 99%
“…lengőtengely körül történik, ez utóbbi a mozgás minden pillanatában vándorol, és kölcsönösen merőleges a fenti két tengelyre. A tibia keresztirányú tengelye a rotáció kiindulási állapotát határozza meg, viszont a görbék alakjára nincs hatással, 8,9 ezért nem okozott problémát a vizsgálataink során, hogy ennek meghatározása hasonlóan bizonytalan, mint a TEA.…”
Section: Eredeti Közleményekunclassified
“…In this domain, automatic shape analysis is strongly advocated because it offers the opportunity to detect morphological and clinical landmarks (MCL) with superior repeatability in comparison to human operators. It has been shown that manual interaction is commonly time consuming, and that the results are mostly dependent upon the examiner's individual expertise and are affected by noticeable inter-observer variability [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%